La angustia por la causa (2011)
ABSTRACT: The present work tries to show how after every foundation act a loss appears, a memory that they pretend to forget from various human speeches, including scientific discourse; nevertheless, this that continue and is expected to be forgot is exact-ly what return to make incomplete, to disarrange the completeness imaginary of the desire person. Mentioned return and subtraction operation, of un-completeness, is the generator factor of angst, inherent to the symbolic record. Understanding this feeling and the movement of the human foun-dation, Lacan creates the “a” in his algebra, cause operator and object by itself that moves inside the real record.